Elizabeth (Betty) Loosley: Adult Education and Research Excellence - Leona M. English (Adult Education Research Conference, 2018)
Elizabeth (Betty) Wyeth Magee Loosley (1911-1994) was an artist and researcher, and one of the best educated women working with the Canadian Association for Adult Education (CAAE, founded 1935) in the 1950s and 1960s. This paper uses archival and interview data to examine her achievements and contributions to the CAAE. This study helps us understand our field’s gendered history and development.
Keywords: gender; writing; research; history; archives